ANALYSIS OF EDUCATIONAL VALUESIN ISLAMIC HISTORICAL LITERACY - Atina Tri Rokhmatin; Dewi Nur Suci (Abjadia : International Journal of Education, 2016)
This research is intended to reveal the educational values in the historical literacy, entitled “Salahuddin Al Ayyubi dan Perang Salib III” written by Alwi Alatas. The educational values exploring the notion of moral, awareness and religion values can be transformed into Islamic History subjects in Madrasah such as Aqidah Akhlaq, Al-Qur’an Al-Hadith, Shariah and Islamic history. Seemingly the same as moral and awareness values, religion values comprise pious, ubudiyah and muamalah that are appropriate to voice the character building as the spirit of curriculum 2013. As the result, it is expected that the learner’s perspectives on their religion history can be explored.  Categorized as Islamic historical genre, this novel does not only promote the awareness on the historical place, language, events, narratives, concept, research skill, contention and contestability. This literacy can familiarize the learners with moral judgement and the ability of self reflection by making connection that relates the past with the self and the world today. يهدف هذا البحث عرض القيم التربوية في الكتاب التاريخي تحت عنوان "صلاح الدين الأيوبي وحرب الصليب الثالث" الذي كتبه علوي العطاس. وعرف أن القيم التربوية يمكن تحويلها إلى المواد التعليمية مثل مادة العقيدة والأخلاق، والقرآن والحديث، والثفاقة الإسلامية. أما القيم الدينية فتحتوي على القيم الإلهية والعبادة والمعاملة. وتفيد هذه القيم في تكوين الشخصية كما قصده المنهج 2013 لأنها تستطلع ملكات الطلاب. ولم يكن هذا الكتاب باعتباره قصة إسلامية يرقي الوعي في المكان واللغة والحادثة والرواية والمفاهيم والبحث والمنازعة والمسابقة فحسب، بل كان هذا الكتاب يعود الطلاب على الأخلاق الدينية ومحاسبة النفس وابتداع الاتصال بين الماضي والحاضر.